Zinc thiazole enhances defense enzyme activities and increases pathogen resistance to Ralstonia solanacearum in peanut (Arachis hypogaea) under salt stress. - Suling Sang; Shaojian Li; Wanwan Fan; Na Wang; Meng Gao; Zhenyu Wang (PLoS ONE)
Crop plants always encounter multiple stresses in the natural environment. Here, the effects of the fungicide zinc thiazole (ZT) on propagation of Ralstonia solanacearum, a bacterial pathogen, were investigated in peanut seedlings under salt stress. Compared with water control, salt stress markedly reduced pathogen resistance in peanut seedlings. However, impaired pathogen resistance was alleviated by treatment with dimethylthiourea, a specific ROS scavenger, or ZT. Subsequently, salt stress or combined salt and pathogen treatment resulted in inhibition of photosynthesis, loss of chlorophyll and accumulation of thiobarbituric acid reactive substances, which could be reversed by ZT. In addition, ZT treatment suppressed the salt stress up-regulated Na+ content and Na+/K+ ratios in peanut roots. Furthermore, salt stress or combined salt and pathogen treatment impaired the activities of antioxidant (e.g. superoxide dismutase/SOD and catalase/CAT), and defense-related (e.g. phenylalanine ammonia lyase /PAL and polyphenol oxidase/PPO) enzymes, which could be rescued by addition of ZT. In contrast, only slight changes of SOD and CAT activities were observed in pathogen-infected seedlings. Similarly, activities of PAL and PPO were slightly modified by salt stress in peanut seedlings. These results suggest that the ZT-enhanced pathogen resistance can be partly attributed to the improvement of photosynthetic capacity and defense enzyme activities, and also the inhibition of Na+/K+ ratios, in this salt-stressed crop plant.